IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM KURIKULUM MERDEKA - Ar Rizqi, Fathir Naufal; Larasati, Suci Indah; Selvi, Selvi; Ayu, Raden Adjeng; Sahroni, Deni; Suhardi, Suhardi (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
The Project to Strengthen the Profile of Pancasila Students (P5) is an integral component of the Merdeka Curriculum, aiming to cultivate students with strong character, independence, and readiness to face 21st-century challenges. This study aims to explore the implementation of P5 in Indonesian educational settings, focusing on implementation strategies, teacher and student involvement, and the challenges encountered. The research method employed is a literature review of academic sources, educational policies, and field practices. Findings indicate that P5 has created more contextual and participatory learning spaces, yet several obstacles remain, including limited human resource readiness, conceptual understanding, and infrastructure support. Continuous professional development for educators, strengthened school management, and consistent policy support are essential to ensure the successful implementation of P5. This study is expected to serve as a reference for improving P5 implementation strategies across various educational levels.